Real Time ASL (American Sign Language) Recognition - Ansari, Fatima; Mistry, Anwar Hussain; Mirkar, Yusuf; Merchant, Alim (International Journal of Computer Sciences and Engineering, 2019)
Hand gestures are powerful means of communication among humans and sign language is the most natural and expressive way of communication for dumb and deaf people. Thus, it provides a replacement for speech among deaf and mute people, but no one form of sign language is universal. American Sign Language (ASL) is one of the sign languages which is the most widely used sign language among the English-speaking community. ASL is also widely learned language, serving as lingua franca. The communication between the deaf /dumb and normal people is extremely poor due to the fact that there is no single standalone platform that can bridge the communication gap. Sign language is a way to bridge this gap still cannot a success since the normal people ever learned such sign languages. One of the ways to eradicate this gap is by identifying the sign language’s hand gestures thus predicting the language for the normal people. In this way, the normal person will be aware of the dumb and deaf’s speech and can respond appropriately. Such a solution will eliminate the level of dependencies which a deaf/dumb person has on a translator for communicating which in turn will provide job opportunities and eradicate many more problems faced by such people in their everyday life.